Georgia : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
During the twin crises of 2008-09 Georgia's foreign exchange reserves have been exposed to a number of external and internal drains. Its exports declined by 21 percent from peak to trough. Bank deposits declined by more than 20 percent in late 2008-early 2009, while deposit dollarization increased sharply. FDI declined from 16.4 percent of GDP in 2007 to an estimated 5 percent of GDP in 2010. Georgia was able to limit the impact of these drains on its international reserves.